To determine the efficacy of homoeopathic remedies for chronic rhinosinusitis, researchers conducted a randomized, placebo-controlled, parallel-arm experiment (Indo-American Journal of Life Sciences and Biotechnology, 2024)
Background: One major health issue that affects people's health-related quality of life is chronic rhinosinusitis (CRS). This research aims to evaluate the effectiveness of individualized homoeopathy (IH) on LM potency in chronic renal failure (CRF). Methods: From July 2012 to December 2013, four institutions conducted a randomized, double-blind, placebo-controlled study on CRS patients. Sixty people met the criteria and were randomly assigned to either receive IH in LM-potencies or a comparable placebo. Area under the curve (AUC) for total symptoms score (TSS) and sinus nasal outcome test 22 over a 3-month period was the primary outcome measure. For the analyses, the intention-to-treat method was used. The results showed that the homoeopathy group had a lower TSS AUC over 3 months compared to the placebo group, but this difference was not statistically significant (IH: 1303.1 ± 612.2; P = 1380.1 ± 811.8; 95% CI: −336.9, 182.9; P = 0.56). In favor of homoeopathy, there was a statistically significant difference between the absolute change in TSS from baseline at days 60 and 75, with a mean difference of 4 (95% CI: 0.3-7.7, P = 0.03) and 3.8 (95% CI: 0.1-7.5, P = 0.04), respectively. At day 75, the investigator and patient both noted significant improvements; at day 60, the difference was 0.5 (95% CI: 0.27-0.84, P = 0.0001), and at day 75, the difference was 0.6 (95% CI: 0.27-0.86, P = 0.0001). In the homoeopathy group, there was a noticeable upward trend in the rhinoscopy score (mean difference: 0.9, 95% CI: −0.00-1.8, p=0.05). Scores on computed tomography scans of the paranasal sinuses were similar between groups. The results of this study suggest that individuals with CRS may benefit from using homoeopathic treatments that are tailored to their specific needs, and the research should continue in this direction.